Pembentukan Badan Hukum Kelompok Masyarakat Penerima Bantuan KKP Republik Indonesia - Wulansari, Dewi Ajeng; Mahfud, Muh. Afif (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research was conducted to aim of exploring the role of notary in the formation of legal entity association as receiver from the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia’s distribution in accordance with Peraturan Menteri Kelautan dan Perikanan Republik Indonesia Nomor 2 Tahun 2021 Tentang Penyaluran Bantuan Pemerintah di Lingkungan Kementerian Kelautan dan Perikanan and to analyze the suitable form of receiver’s legal entity accordance with the requirements set by the Ministry. This research uses normative law and descriptive with descriptive qualitative as the type of research. The data collection methods used were library research and document analysis and conducted using qualitative analysis methods. The result of this study showed that the notary might acts in making the deed of association’s establishment or other legal entity desired by the public who comes to the notary with the procedures; making a deed of association to register the association until it can be registered at the database system of the Ministry of Law and Human Rights until it becomes valid. Notary plays a role in helping people who need assistance from the Ministry of Maritime Affairs and Fisheries to meet the requirements to give legal status to the establishment of their group.